Sufism and healing - Mitha, Karim (Journal of spirituality in mental health, 2019)
The aspect of individual patient experience in health care has taken on greater role in contemporary times. Due to an increasingly diverse patient population, medical professionals are encountering individuals who utilize other forms of healing practices in addition to allopathic models of care. This is particularly relevant in mental health care, where concepts of "healing," "well-being," and "wellness" come to fore. This article examines the Islamic concept of Sufism, tasawwuf, and how concepts such as dhikr (recitation) and knowing one's self can be overlayed to psychological principles of mindfulness and self-efficacy-showcasing the intersection of spirituality and mental health.